Basel Agreements and development banks in Brazil: An Assessment of BNDES and BNB - Sobreira, Rogério; Norberto Montani Martins (Revista de administração pública (Rio de Janeiro), 2011)
In Brazil, development banks were subject to the regulatory requirements of Basel Accords and treated similarly to other institutions belonging to the Brazilian financial system. However, given the idiosyncratic nature of development banks it is often argued that the implementation of agreements of this type to these institutions is not adequate, as long as it could prevent them from fulfilling their mission effectively. Therefore, this article aims to assess whether the submission of two major Brazilian development banks, BNDES and BNB, to the Basel regulatory framework caused a loss of dynamism of these institutions in order to prevent full or partial compliance with its functions. We conclude that the two institutions mentioned were affected asymmetrically by the regulatory requirements associated with Basel Accords, allowing the BNDES to exercise its functions with some little limitation, but heavily damaging the BNB in the exercise of its functions as a development bank.